Use of rating assessment of financial and economic operation effectiveness of the JSC “RZD” branches - P. A. Shanchenko; K. O. Vinnikova; E. V. Ershova; I. N. Lenskaya (Вестник Научно-исследовательского института железнодорожного транспорта)
Rating is one of the methods of economic analysis used for comparative assessment of effectiveness of production and economic operation of the organizational structures in different branches of economy. Rating assessment of railways is used in JSC “RZD” since 2018 for objective assessment of economic and financial sustainability and effectiveness of management of structural divisions (branches). Methods of rating assessment adapted for structural divisions of JSC “RZD” with regard to the specificity of their operation are examined in the work.Main objectives of establishing the rating assessment system of financial and economic operation of the JSC “RZD” branches are examined, detailed rating classification is presented.Basic principles are developed for establishing the rating assessment system of operation effectiveness of the deputies of the JSC “RZD” branches heads in terms of financial and economic operation, as well as classification of indicators of financial and economic operation of the JSC “RZD” branches by types of operation with definition of their vector orientation.The following conclusions are made: 1. Presented rating assessment is an indicator of the quality of financial and economic operation management of the JSC “RZD” branches. 2. Use of rating assessment for results analysis is relevant for motivation of the management in charge for economic operations. 3. Further development of the rating assessment system consists in establishing the events classifier and optimization of the current expenses.